2017
DOI: 10.1073/pnas.1613937114
|View full text |Cite
|
Sign up to set email alerts
|

Diverse evolutionary patterns of pneumococcal antigens identified by pangenome-wide immunological screening

Abstract: Characterizing the immune response to pneumococcal proteins is critical in understanding this bacterium's epidemiology and vaccinology. Probing a custom-designed proteome microarray with sera from 35 healthy US adults revealed a continuous distribution of IgG affinities for 2,190 potential antigens from the species-wide pangenome. Reproducibly elevated IgG binding was elicited by 208 "antibody binding targets" (ABTs), which included 109 variants of the diverse pneumococcal surface proteins A and C (PspA and Ps… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
135
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(148 citation statements)
references
References 77 publications
5
135
1
Order By: Relevance
“…Table 3 shows the genes which were significant in this combined analysis using any of our association methods. The genes noted in bold font in table 3 are all immunogenic 32 , and have all previously been associated with pneumococcal virulence in animal models [33][34][35][36] , but this is the first time an association has been shown in patients with invasive disease. Previous conclusions, drawn from protein binding to the Laminin receptor, have suggested that pspC ( cbpA ) is necessary for meningitis 37 .…”
Section: Identification Of Pneumococcal Invasiveness Loci In Multiplementioning
confidence: 99%
See 4 more Smart Citations
“…Table 3 shows the genes which were significant in this combined analysis using any of our association methods. The genes noted in bold font in table 3 are all immunogenic 32 , and have all previously been associated with pneumococcal virulence in animal models [33][34][35][36] , but this is the first time an association has been shown in patients with invasive disease. Previous conclusions, drawn from protein binding to the Laminin receptor, have suggested that pspC ( cbpA ) is necessary for meningitis 37 .…”
Section: Identification Of Pneumococcal Invasiveness Loci In Multiplementioning
confidence: 99%
“…We then used GWAS to find locus effects on invasive disease, independent of serotype. As pneumococcal genomes vary extensively in their pan-genome 30 , as well as having phenotypically important mosaic structural variants 31 and antigens alleles 32 , we used a combination of methods to catalogue the population level variation then tested for associations while adjusting for population structure. We first performed this GWAS with disease severity, which was only measured in the Dutch cohort.…”
Section: Identification Of Pneumococcal Invasiveness Loci In Multiplementioning
confidence: 99%
See 3 more Smart Citations